Optimization and identification of siderophores produced by Pseudomonas monteilii strain MN759447 and its antagonism toward fungi associated with mortality in Dalbergia sissoo plantation forests - Srivastava, Pragati; Sahgal, Manvika; Sharma, Khanchand; Enshasy, Hesham Ali El; Gafur, Abdul; Alfarraj, Saleh; Ansari, Mohammad Javed; Sayyed, R. Z. (Frontiers in Plant Science, 2022)
Siderophore-positive bacteria present in the rhizosphere and in bulk soil assist plants by either inhibiting phytopathogen proliferation or increasing plant growth. The bacterial diversity of the Shisham forest ecosystem in the Tarai region of the Western Himalayas was studied and used for siderophore production, taking into account the large-scale dieback and wilt-induced mortality in Dalbergia sissoo (common name: shisham) plantation forests and the importance of soil microbes in tree health. In addition, Pseudomonas, Burkholderia, and Streptomyces were prominent siderophore-positive bacteria in Shisham forests. Pseudomonas species are known for their remarkable siderophore-producing ability. Bacterial siderophores inhibit pathogen growth by rapidly lowering the number of ferric ions in the rhizosphere. The Pseudomonas monteilii strain MN759447 was isolated from a D. sissoo plantation forest at the Agroforestry Research Centre, Pantnagar, Uttarakhand (28°58′N 79°25′E/28.97°N 79.41°E). It produces a significant number of siderophore units (80.36% in total). A two-stage optimization of growth factors was attempted in the strain MN759447 for better siderophore recovery. In the first-stage single-factor experiment, among the five variables studied, only pH, NH4NO3 concentration, and Fe concentration affected siderophore synthesis. In the second stage, an optimization of pH, NH4NO3 concentration, and Fe concentration for improved growth and enhanced siderophore production was carried out using a Box–Behnken design with response surface methodology. By using LC-MS, two derivatives of pseudomonine, salicylic acid, and kynurenic acid were detected as siderophores in the purified XAD-2 methanol extract of the P. monteilii strain MN759447. In addition to siderophore production, the P. monteilii strain MN759447 also exhibited a broad range of antagonistic activity against Aspergillus calidoustus (65%), Fusarium oxysporum (41.66%), Talaromyces pinophilus (65%), and Talaromyces verruculosus (65.1%) that are linked to sissoo mortality. To our knowledge, this is the first report on siderophore-producing bacteria isolated, identified, and characterized from the D. sissoo Roxb. forest habitat. This strain can also be developed as a commercial product.